Implementation of Pancasila Student Profile in Dance Arts Extracurricular at SDN Wates 01 - Munawar, Bunga Muawanah; Ramadhani, Niken Aulia; Utami, Apriliana Prili; Ristiani, Rima; Nuraini, Widya; Cahyaningtyas, Andarini Permata (Jurnal Riset Ilmu Pendidikan, 2025)
This study aims to describe the implementation of the values of the Pancasila Student Profile through extracurricular dance activities at SD Negeri Wates 01. The Pancasila Student Profile consists of six main dimensions: having faith in and devotion to God Almighty with noble character; independence; critical thinking; creativity; collaboration; and global diversity. Extracurricular dance activities were chosen as a strategic medium for instilling these values, as traditional dance involves cultural appreciation, cooperation, discipline, and self-expression. This research employed a descriptive qualitative method with data collected through observation, interviews, documentation, and questionnaires. The results show that the extracurricular dance program effectively fosters the values of the Pancasila Student Profile, particularly in the areas of religious character, independence, teamwork, and global diversity. However, the dimensions of critical thinking and creativity still require further development. The implementation of this program is supported by thorough planning, structured execution, and regular evaluations involving the principal and extracurricular supervisors. In conclusion, the extracurricular dance program at SDN Wates 01 serves as an effective platform for strengthening students' character in line with Pancasila values.